2012
DOI: 10.4319/lom.2012.10.767
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the light: The effects of particles, dissolved materials, and temperature on in situ measurements of DOM fluorescence in rivers and streams

Abstract: Field-deployable sensors designed to continuously measure the fluorescence of colored dissolved organic matter (FDOM) in situ are of growing interest. However, the ability to make FDOM measurements that are comparable across sites and over time requires a clear understanding of how instrument characteristics and environmental conditions affect the measurements. In particular, the effects of water temperature and light attenuation by both colored dissolved material and suspended particles may be significant in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
226
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(243 citation statements)
references
References 24 publications
14
226
2
1
Order By: Relevance
“…6). Prior work has demonstrated the interference of turbidity with fDOM measurement (Downing et al, 2012); we found low correlation (r 2 =0.08) between fDOM and turbidity at this site. Significant wave height approached 0.1 m, peaking daily during periods of winds from the south (Fig.…”
Section: Temporal Variability Of Light Attenuation Constituents Andcontrasting
confidence: 38%
“…6). Prior work has demonstrated the interference of turbidity with fDOM measurement (Downing et al, 2012); we found low correlation (r 2 =0.08) between fDOM and turbidity at this site. Significant wave height approached 0.1 m, peaking daily during periods of winds from the south (Fig.…”
Section: Temporal Variability Of Light Attenuation Constituents Andcontrasting
confidence: 38%
“…Lagrangian sampling of rivers could be useful for determining OM transformation hotspots (both new sources and processing) within a river channel, that could then lead to more intense investigations of sources and processing at those hotspots. Continual advancements in sensors that allow high temporal and spatial monitoring of colored DOM (CDOM) properties in rivers will undoubtedly help in capturing the complexity of river systems (Downing et al, 2012;Pellerin et al, 2012), but in spite of their potential, CDOM and fluorescent DOM (FDOM) by themselves have proven elusive in giving the chemical specificity that is needed to truly understand DOM dynamics. On the other hand, such sensors could also be used as targeting agents to point toward regions where chemical analyses can be put to the greatest use (Hernes et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…4A). Such a plateau is likely due to light attenuation from increasing concentrations of colored dissolved material (Downing et al, 2012;Pereira et al, 2014). The suspended sediment concentration was found to account for most of the difference between in situ and filtered ex situ FDOM measurements (Fig.…”
Section: Methodsmentioning
confidence: 95%